A non-regional perspective on bilateral relations between states from different regions: a case study of Malaysia-Saudi Arabia relations - Asmady Idris; Omer Kurtbag (IDOSI Publications, 2014)
This study attempts to introduce a new approach of analyzing bilateral relations between states from different regions, Malaysia and Saudi Arabia, by formulating a ‘non-regional perspective’ which is extracted from debates on regionalism. Throughout the discussion, the study has found that the non-regional elements are capable of influencing Malaysia’s relations with Saudi Arabia in the international system and also with the indication that the element of ‘historically essential’ has been more prevalent than ‘accidentally essential’. Despite this, both elements are still very much related to the connotation of the non-regional perspective in analyzing bilateral relations between states from different regions.